Following Putnam's trail : on realism and other issues - Rivas Monroy, Ma. Uxía (María Uxía); Cancela Silva, Celeste; Martínez Vidal, Concha (Poznań studies in the philosophy of the sciences and the humanities ;, 2008)
"Following Putnam's Trail addresses Putnam's path through important philosophical problems. One outstanding feature of Putnam's philosophy has been his contribution to the development of American pragmatism as well as bis many changes of mind when thinking about realism. Realism and pragmatism are indeed the central focus of the contributions to the volume. The book includes a defence of pragmatism by Putnam himself, and several commentaries on it. This volume should be of interest both to scholars who specialize in analytical philosophy as well as to those who have a wider interest in philosophy."--Jacket